The Role of Accounting Conservatism in Moderating the Determinants of Earning Quality - Cahyani, Elisabeth Putri Adilya; Khafid, Muhammad (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
The purpose of this research is to examine the effect of liquidity, profit growth, firm size, and board of commissioners on the quality of earnings with conservatism as a moderating variable. The population of this study was the manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. Sampling of the research used purposive sampling method has obtained 59 sample companies with 4 years of observation so that 239 units of analysis were obtained. The total unit of analysis was reduced by 103 outlier data, so that the data used became 133 data. The analysis techniques used in the research were descriptive statistical analysis technique and inferential regression analysis with moderating variable. The results show that liquidity, profit growth, and the board of commissioners have no effect on the quality of earnings. Meanwhile, accounting conservatism does not moderate the effect of liquidity and firm size on earnings quality. The failure of accounting conservatism as the moderating variable in this research model is interesting to be carried out by the further research by developing the appropriate conservatism measurement according to the characteristics of manufacturing companies.Ã‚Â